HUBUNGAN DUKUNAGN EMOSIONAL KELUARGA TERHADAP KUNJUNGAN LANSIA KE POSYANDU LANSIA DI GUNUNG SEMPU KELURAHAN TAMAN TIRTO KASIHAN BANTUL YOGYAKARTA. - Pratiwi Gasril (Sistem Informasi, 2018)
Emotional support of the family is a safe and peaceful place to rest and also calm the mind . T u juan this study to determine the relationship of emotional support for their families to visit the elderly to posyandu l Ansia Mount Sempu Village Tamantirto Poor Bantul, Yogyakarta. This research is non experimentalresearch that is correlation research by using cross sectional approach . The instrument used in this study is a questionnaire for support emotional family and elderly visits seen from elderly visit from posyandu elderly. Sampling technique method used probality or random sample with 33 respondents and 10 respondents family. Dengunakan data analysis univariate, bivariate and analasisi and statistical tests digunak a n is the Chi-square test. Result of research of relation of emotional support of family to visit lansi at posyandu elderly, got result of existence of meaningful relation from support arga emotionally numb with ( p value = 0.02) . From the results of this study can be concluded that the elderly who visited the posyandu elderly need family support, especially emotional support, which can increase the spirit and motivation of elderly to visit posyandu elderly.